BookMark: Appropriating existing infrastructure to facilitate scalable indoor navigation. Issue 103 (July 2017) - Pearson, Jennifer; Robinson, Simon; Jones, Matt
Abstract: This paper describes an approach to using physical-digital appropriation for navigation, piggybacking off the humble, ubiquitous barcode to facilitate cheap, scalable indoor wayfinding. We illustrate the technique by describing a prototype interface for navigating to specific books within a library. Our design—BookMark—provides visitors to the library with a detailed map to any desired book by simply scanning the barcode on the back of any other book in the library. After describing in detail how our technique is achieved, we move on to show its effectiveness via an in-situ experiment in which we compare our design to standard methods of library navigation. We then present the results of a longitudinal evaluation where we deploy the BookMark application to library visitors for a period of 24 months. We conclude with a discussion of our overall results, what our design means for other pervasive infrastructures, and how best to design for the future of physical-digital appropriation. Abstract : Graphical abstract: Abstract : Highlights: Provides a novel approach to indoor navigation by appropriating existing infrastructure. Demonstrates the viability of the approach via a two-year deployment. Discusses benefits of the technique, and implications for future designs.